2009
DOI: 10.1002/anie.200805780
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Divergent Reactivity of Aryl–Palladium Intermediates for the Rapid Assembly of Fluorene and Phenanthrene Derivatives

Abstract: They all fall down: The value of domino processes can be greatly enhanced when the possibility exists for one to selectively diverge from a common intermediate. In preliminary studies the dual reactivity of aryl-palladium intermediates is exploited. A diverse array of fluorene and phenanthrene derivatives were synthesized in a rapid and efficient manner (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…We are highly interested in the development of cross‐coupling reactions for material science and we realized that domino reactions such as norbornene(NBE)‐mediated palladium cascades hold great potential for not only tackling the sequential reactions in one pot, but also providing access to the ubiquitous aryl halides. However, the homo‐coupling of aryl halides might be facile, while directing groups, which assist in the controlled heterobiaryl coupling, might be difficult to be removed after reactions . Recently, the use of a carboxylic acid as traceless directing group has received significant attention and Hong's group recently demonstrated this strategy with an impressive tandem synthesis of acenes (Scheme c) .…”
Section: Methodsmentioning
confidence: 99%
“…We are highly interested in the development of cross‐coupling reactions for material science and we realized that domino reactions such as norbornene(NBE)‐mediated palladium cascades hold great potential for not only tackling the sequential reactions in one pot, but also providing access to the ubiquitous aryl halides. However, the homo‐coupling of aryl halides might be facile, while directing groups, which assist in the controlled heterobiaryl coupling, might be difficult to be removed after reactions . Recently, the use of a carboxylic acid as traceless directing group has received significant attention and Hong's group recently demonstrated this strategy with an impressive tandem synthesis of acenes (Scheme c) .…”
Section: Methodsmentioning
confidence: 99%
“…Seminal work by Lautens has shown that such an aryl-Pd(II) species could attack an adjacent carbonyl group, but this has been limited to an intramolecular transformation. 15 Clearly, many challenges can be envisioned with this redox-neutral strategy, including the difficulty of controlling site-selectivity and the choice of suitable electrophiles. Thus, at this preliminary stage, we have been focused on a simplified system with one electrophile being a proton source (Scheme 1D).…”
Section: The Bigger Picturementioning
confidence: 99%
“…Lautens et al in 2009 reported that norbornene mediated CÀ H activation accesses the substituted fluorenone (54) from obromobenzaldehyde (49) or o-bromo aryl ester (53) with 1iodonaphthalene (52) by changing catalyst composition and reaction conditions (heating reaction medium at 150°C in microwave reactor) (Scheme 11). [34] Recently Sorensen et al reported the transient directing group mediated fluorenone synthesis via double CÀ H activation. Anthranilic acid acts as a transient directing group (Scheme 12).…”
Section: Intermolecular Synthesis Of Fluorenonesmentioning
confidence: 99%